Les perífrasis modals de necessitat-obligació i probabilitat en català. Seguiment diacrònic. Segles XIII al XX - Cabanes Fito, Vicent (Caplletra. Revista Internacional de Filologia, 1996)
The analysis presents a serie of systematized information which helps to retrace the application frequency that modal periphrasis deure + infinitive, haver + infinitive and tenir + de + infinitive have reached from 13th to 20th centuries, their formal variants and functional changes. It has also analysed another periphrastic structures that eventually they join Catalan modal periphrastic system, and it has been examined some specific aspects of the analysis: the notion of verbal periphrasis, the variations that involve modal variables and the others that belong to deure + infinitive syncretic form, the monitoring in cult and late Latin of periphrastic forms with the habeo and debeo verb, in addition to the use of modal indicators, the repetition of periphrastic forms in the syntagmatic sequence, nexus variables, syncretic structures and some analogical process.